2020
DOI: 10.3389/fenrg.2020.594857
|View full text |Cite
|
Sign up to set email alerts
|

Tackling xEV Battery Chemistry in View of Raw Material Supply Shortfalls

Abstract: The growing number of Electric Vehicles poses a serious challenge at the end-of-life for battery manufacturers and recyclers. Manufacturers need access to strategic or critical materials for the production of a battery system. Recycling of end-of-life electric vehicle batteries may ensure a constant supply of critical materials, thereby closing the material cycle in the context of a circular economy. However, the resource-use per cell and thus its chemistry is constantly changing, due to supply disruption or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…The available literature covering the current and historical market share (2015-2020) of LIBs is rather scattered. In this work, we take an average market share for each chemistry from the sources analyzed [4,6,7,[44][45][46][47], for the periods 2015, 2020 and 2030, combined with interpolations for the years within this range to define yearly market share. In addition, we define two more reference years for the interpolations until 2050, more precisely defining market share for the years 2040 and 2050.…”
Section: Ev Fleet and Battery Scenario Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature covering the current and historical market share (2015-2020) of LIBs is rather scattered. In this work, we take an average market share for each chemistry from the sources analyzed [4,6,7,[44][45][46][47], for the periods 2015, 2020 and 2030, combined with interpolations for the years within this range to define yearly market share. In addition, we define two more reference years for the interpolations until 2050, more precisely defining market share for the years 2040 and 2050.…”
Section: Ev Fleet and Battery Scenario Definitionmentioning
confidence: 99%
“…Hence, the full (or partial) replacement of the current LDV fleet with EVs will require the quick expansion of the production capacity of the battery industry, which in turn requires robust value chains for primary raw material mining and processing. The likely future raw material demand and the challenges related to the supply required for the transition to electric mobility have been covered in several reports and peer-reviewed articles [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Current estimates on the global installed production capacity for LIBs span from 250 GWh/year [16] to 640 GWh/year [6].…”
Section: Introductionmentioning
confidence: 99%
“…The circular use of components and materials offers big economic opportunities and has great potential to secure the supply of strategic raw materials for cell manufacturers [3]. The work of Sato and Nakata [4] showed that by 2035, high quantities of critical materials for the production of new Li-ion batteries in Japan will be obtained from the recycling of batteries at the end-of-life (EoL) stage (34% of lithium (Li), 50% of cobalt (Co), 28% of nickel (Ni), and 52% of manganese (M)).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the label NMC 532 indicates that the cathode comprises five parts nickel, three parts manganese, and two parts cobalt. The percentage after the code NCA (nickel cobalt aluminum oxide) describes the material share of cobalt within the cathode [9].…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on cathode chemistries that either already have a high market share or will be important in the near future. Thus, solid-state batteries and other innovative cell generations, such as lithium air, are neglected, although they are expected to gain significant market shares in the future [9]. This is because no market-ready battery has been developed yet and, according to forecasts, they will initially become relevant in 2030 [9].…”
Section: Introductionmentioning
confidence: 99%